Comparative biochemical analysis of Vignamungo(l.) Hepper and Vignaaconitifolia(jacq.) Marechalunder salt stress - SAROJ MEENA; CHANDRA PRAKASH SHARMA; DR. SOUMANA DATTA (International Journal of Pharma and Bio Sciences, 2017)
Soil salinity affects plant growth and development due to harmful ion effects and water stress caused by reduced osmotic potential in the soil solution. In order to evaluate effects of salt stress on several morphological parameters, total soluble sugar and accumulation of proline in Vigna mungo and Vigna aconitifolia plantlets, studies were undertaken under control and salinity stress condition. The seeds were grown in pots and irrigated with water till 7 days and after that plantlet were treated with 50, 100 and 150mM of NaCl solution. The stress induced by high concentration of Na+ and Cl- ions caused inhibition of cell division and cell expansion through abscisic acid presence, closure of stomata, and decline in photosynthesis. Salinity negatively affected the leaf area and chlorophyll content while the amount of free proline and carbohydrate increased significantly with increased salinity level.